Controllable end shape modification of ZnO nano-arrays/rods by a simple wet chemical etching technique. (18th August 2015) - Sun, Jingchang; Zhao, Ting; Ma, Zhangwei; Li, Ming; Chang, Cheng; Liang, Hongwei; Bian, Jiming; Li, Chengren
Abstract: The well-aligned ZnO nano-arrays/rods synthesized by a chemical bath deposition method on a highly conductive Si substrate were chemically etched in an ammonia chloride aqueous solution. An obvious end shape modification of ZnO nano-arrays/rods was realized in this report. The hexagonal frustum end of ZnO nano-arrays/rods changed into a pyramid and the diameter of ZnO nano-arrays/rods decreased gradually with the increasing etching time. The evolution mechanism of the wet etching process was discussed based on a proposed evolution model. Photoluminescence measurements indicated that the near band edge emissions of ZnO nano-arrays/rods increased greatly after wet etching. The controllable end shape modification of ZnO nano-arrays/rods on a highly conductive Si substrate by this simple wet etching technique will further explore the application of ZnO in field emission devices and 1D based nano-devices with various end shapes.